Treatment of Atlantoaxial Dislocation in Children with Down Syndrome Using Posterior Atlantoaxial Screw Fixation - Li, Chengxin; Tian, Yiren; Ren, Qiang; Ji, Xiangqian; Mao, Ziwei; Wu, Ming (Frontiers in Surgery, 2022)
Background: To investigate the effect of posterior atlantoaxial screw fixation for the treatment of atlantoaxial dislocation in children with Down syndrome (DS). Methods: Children diagnosed with DS who underwent posterior atlantoaxial screw fixation or occipitocervical fusion from January 2017 to January 2020 in Hebei Children’s Hospital were retrospectively included. Preoperative CT and MRI were performed to check the os odontoideum (OsO) and spinal cord compression, signal changes and spinal cord injury grade (ASIA grade). Results: All 5 children have atlantoaxial dislocation and OsO. Among which 60% (3/5) children had changes in spinal cord signals, and 40% (2/5) had dural sac compression. Every child underwent posterior atlantoaxial screw fixation (3.5-mm diameter), and the average fusion level was 1.8 (1-2). All 5 cases wore the head-neck-chest brace for 3-6 months after the operation. 1 case had dural tear, and recovered well after timely suturing. 1 case had internal fixation breakage of the prosthetic joint and underwent revision surgery. At the last follow-up, all cases were fused and the neurological function were all ASIA grade E. Conclusion: After posterior atlantoaxial screw fixation, fusion and nerve recovery were achieved in all children with atlantoaxial dislocation and OsO. Postoperative head-neck-chest braces are necessary in children, especially those with occipitocervical fusion.